Connecting histories in Afghanistan market relations and state formation on a colonial frontier - Hanifi, Shah Mahmoud (Stanford University Press, 2011)
Most histories of nineteenth-century Afghanistan argue that the country remained immune to the colonialism emanating from British India because, militarily, Afghan defenders were successful in keeping out British imperial invaders. However, despite these military victories, colonial influences still made their way into Afghanistan.